Small Islands – Big Problem: Senkaku/Diaoyu and the Weight of History and Geography in China-Japan Relations - Gavan McCormack (Japan Focus, 2011)
In December 2010, the Okinawan city of Ishigaki (within which Japanese administrative law incorporates these islands) adopted a resolution to declare 14 January to be “Senkaku Islands Colonization Day.” The “Colonization Day” is intended to commemorate the incorporation of the islands by cabinet decision 116 years earlier. China immediately protested.Ishigaki was following the model of the Shimane Prefectural Assembly, which in 2005 declared a “Takeshima Day” in commemoration of the Japanese state’s incorporation 100 years earlier of the islands known in Japan as Takeshima but in South Korea (which occupies and administers them) as Tokdo. That Shimane decision prompted fierce protests in South Korea. The Ishigaki decision seems likely to do no less in China. Why should these barren rocks, inhabited only by endangered short-tailed albatross, be of such importance to otherwise great powers? Whose islands are they? How should the contest over them be resolved?